Two methods of preparing cottage cheese from non-fat dry milk - Suarez, Monina J.; De Leon, Sonia Y. (1965.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Cottage cheese